An experimental and modeling study of physical N2O solubility in 2-(ethylamino)ethanol. (November 2019) - Xiao, Min; Liu, Helei; Wang, Jialu; Luo, Xiao; Gao, Hongxia; Liang, Zhiwu
Highlights: Physical N2 O solubility in EAE and its aqueous solution was measured. The relationship of amine structural features with N2 O solubility was shown. The N2 O solubility data were correlated and predicted using models. Abstract: Physical N2 O solubility in pure 2-(ethylamino)ethanol (EAE) solvent was measured over the temperature range 289.6– 349.7 K. The physical solubility of CO2 in EAE was then derived via the "N2 O analogy" method. The effect of structural characteristics such as carbon chain length, hydroxyl group, hydroxylmethyl group and amino group on the physical CO2 solubility was revealed through the comparison of various amines to determine the most advantageous structure for high physical solubility. The physical heat of CO2 absorption of the amine was correlated using Arrhenius equation to analyse the sensitivity of the solubility data to the temperature change. Likewise, physical N2 O solubility in aqueous EAE solution was measured from 289.6 to 349.7 K and EAE concentration from 7.5 to 75.0 wt%. To correlate the solubility data in a binary EAE-H2 O system, four mathematical models, polynomial, semi-empirical, Redlich-Kister equation and Arrhenius equation models were introduced with average absolute relative deviation (AARD) of 6.5%, 8.7%, 5.9% and 8.7%, respectively. A small extrapolation with respect to temperature at 283 and 363 K was made to further estimate the performance of these models.